Challenging Intern Nation: A Roundtable with Intern Labour Activists in Canada - Nicole Cohen; Greig de Peuter (tripleC: Communication, Capitalism & Critique)
Internships have gained critical attention in Canada, thanks largely to the efforts of intern labour activists, who have generated media coverage, lobbied and advised politicians, conducted education and outreach, and advocated for an end to the proliferation of unpaid internships in Canada. This roundtable interview with intern labour activists Ella Henry, Andrew Langille, Joshua Mandryk, and Claire Seaborn was conducted by Nicole Cohen and Greig de Peuter in Toronto on March 1, 2015. Follow up interviewing was conducted over e-mail in May 2015. The interview has been edited and condensed.